Bilirubin and its Oxidation Products Damage Brain White Matter. Issue 11 (November 2014) - Lakovic, Katarina; Ai, Jinglu; D'Abbondanza, Josephine; Tariq, Asma; Sabri, Mohammed; Alarfaj, Abdullah K; Vasdev, Punarjot; Macdonald, Robert Loch
Brain injury after intracerebral hemorrhage (ICH) occurs in cortex and white matter and may be mediated by blood breakdown products, including hemoglobin and heme. Effects of blood breakdown products, bilirubin and bilirubin oxidation products, have not been widely investigated in adult brain. Here, we first determined the effect of bilirubin and its oxidation products on the structure and function of white matter in vitro using brain slices. Subsequently, we determined whether these compounds have an effect on the structure and function of white matter in vivo. In all, 0.5 mmol/L bilirubin treatment significantly damaged both the function and the structure of myelinated axons but not the unmyelinated axons in brain slices. Toxicity of bilirubin in vitro was prevented by dimethyl sulfoxide. Bilirubin oxidation products (BOXes) may be responsible for the toxicity of bilirubin. In in vivo experiments, unmyelinated axons were found more susceptible to damage from bilirubin injection. These results suggest that unmyelinated axons may have a major role in white-matter damage in vivo. Since bilirubin and BOXes appear in a delayed manner after ICH, preventing their toxic effects may be worth investigating therapeutically. Dimethyl sulfoxide or its structurally related derivatives may have a potential therapeutic value at antagonizing axonal damage after hemorrhagic stroke.